Does Enhancing of the Competitiveness Influence on Foreign Direct Investments in Western Balkan Countries? - Zlatković, Matea (European Journal of Multidisciplinary Studies, 2016)
Foreign direct investments present a valuable source of national competitiveness as they have attributes of capital flows provide knowledge and technology transfer from one country to target country. In this paper are used variables defined by World Economic Forum which construct Global Competitiveness Index for assessing competitiveness of the country. The purpose of the research is to examine does the national competitiveness increase enhance the level of FDI flows in transition Western Balkan economies that are not yet full members of European Union. The findings claim that larger increase in FDI per capita stocks in majority analyzed countries would have if making infrastructure more competitiveness, accelerate their technological readiness and improve innovation while certain countries should work on health and primary education and higher education and training. According to the results, there is no correlation between FDI flows and macroeconomic environment, institutions, development of financial markets, good market efficiency, labor market efficiency and business sophistication. Applying benchmark method, it is established the most competitive WB country as benchmark value for other transition countries in its neighborhood for enhancing their competitiveness, specially in the regional market. Also, it is obtained what if analysis to detect potential rise of FDI per capita stocks as a consequence of potential changes in some competitiveness variables. It is also calculated the potential increase in FDI/capita due to similar changes in different competitiveness variables.
Keywords: Competitiveness, Foreign Direct Investment, Transition Economies, What If Scenario.